Contamination level, chemical fraction and ecological risk of heavy metals in sediments from Daya Bay, South China Sea. (March 2018) - Liu, Jin-Jun; Ni, Zhi-Xin; Diao, Zeng-Hui; Hu, Yong-Xia; Xu, Xiang-Rong
Abstract: Contamination level, chemical fraction and ecological risk of heavy metals in sediments from Daya Bay (DYB) were conducted in this study. The results revealed that the concentration of Cr, Cu, Zn, As, Cd and Pb in sediments were in the range of 36.38–90.33, 9.54–61.32, 33.54–207.33, 7.80–18.43, 0.13–0.43 and 15.89–30.01 mg kg −1, respectively, with bioavailable fractions of 13.29, 54.16, 47.60, 32.74, 68.14, 26.59%, respectively. A modified potential ecological risk index (MRI) was used for the ecological risk assessment, with ecological risk contribution ratios of 75.73, 14.29, 5.47, 1.74, 1.57 and 1.21% for Cd, As, Cu, Cr, Pb and Zn, respectively. The main contaminants were Cd and As, with their ecological risks "High" and "Moderate" levels, and their enrichment degrees "Moderately Severe" and "Moderate", respectively. The multivariate statistical analysis suggested that the various anthropogenic activities along the bay might contribute mainly to the heavy metals contamination in DYB. Highlights: Heavy metals contamination in sediments of Daya Bay showed an increasing trend. Bioavailability of heavy metals followed the order of Cd > Cu > Zn > As > Pb > Cr. Risk contribution ratios of Cd, As and Cu were 75.72, 14.05, 5.76%, respectively. Results of ecological risks evaluations were High for Cd and Moderate for As. Coastal anthropogenic sources were causes of heavy metals contamination in DYB.